Analisis Potensi Pengembangan Aerotropolis di Bandar Udara Internasional Kualanamu Medan - Minda Mora; Ali Murtadho (Research and Development Agency of The Ministry of Transportation, 2015)
Kualanamu International Airport is one of the airports in Indonesia, which has the potential to be developed into Aerotropolis Airport. This study aims to analyze the potential development of aerotropolis in Kualanamu International Airport Medan. Potential analysis is done with 2 (two) approaches, namely the ratio of non-aeronautical revenues and the average consumption of passengers. Analysis of the potential development of aerotropolis in Kualanamu Medan Airport shows the ratio of nonaeronautical revenue contribution to total revenue the airport from 2010 to 2014 lagged up to 42.86% of the proportion of revenue Amsterdam Airport Schiphol. At the viability projections in 2019, the International Airport Kualanamu was 16.63% below the Amsterdam Airport Schiphol. Based on these results, the proportion of the contribution of non-aeronautical revenues in Kualanamu Medan from 2010 s.d 2014 adrift far enough away from Amsterdam Airport Schiphol. But the 2019 projection, quite approaching Amsterdam Airport Schiphol. The same condition also occurs for patterns of consumption Kualanamu airport passengers are left pretty much when compared with the consumption patterns of passengers at Amsterdam Airport Schiphol the surrounding region has grown into aerotropolis. That is, the consumption patterns of passengers still have to be improved. Keywords: airport, aerotropolis, kualanamu. Bandara Internasional Kualanamu merupakan salah satu bandar udara di Indonesia yang memiliki potensi untuk dikembangkan menjadi Bandar Udara Aerotropolis. Penelitian ini bertujuan untuk melakukan analisis potensi pengembangan aerotropolis di Bandar Udara Internasional Kualanamu Medan. Analisis potensial dilakukan dengan 2 (dua) pendekatan, yaitu rasio pendapatan non-aeronautika dan rata-rata konsumsi penumpang. Analisis potensi pengembangan aerotropolis di Bandar Udara Kualanamu Medan menunjukkan rasio kontribusipemasukan non-aeronautikal terhadap total pemasukan bandara dari tahun 2010 sampai dengan 2014 tertinggal sampai 42.86% dari proporsi pemasukan Amsterdam Airport Schiphol. Pada proyeksi viability tahun 2019, Bandara Internasional Kualanamu berada 16.63% di bawah Amsterdam Airport Schiphol. Berdasarkan hasil tersebut, proporsi kontribusi pemasukan non-aeronautikal Bandara Kualanamu Medan dari tahun 2010 s.d 2014 terpaut cukup jauh dari Amsterdam Airport Schiphol. Namun pada proyeksi 2019, cukup mendekati Amsterdam Airport Schiphol. Kondisi yang sama juga terjadi untuk pola konsumsi penumpang bandara Kualanamu yang tertinggal cukup jauh jika dibandingkan dengan pola konsumsi penumpang di Amsterdam Airport Schiphol yang kawasan sekitarnya telah tumbuh menjadi aerotropolis. Artinya, pola konsumsi penumpang masih harus ditingkatkan. Kata kunci: bandar udara, aerotropolis, Kualanamu.